Green, Resilient, and Inclusive Development - World Bank (World Bank, Washington, DC, 2021)
Developing countries have experienced growing structural weaknesses over the last decade. COVID-19 and climate change have further aggravated these, worsening poverty and inequality, and starkly exposing the interdependence between people, the planet, and the economy. This report charts out the Green, Resilient, and Inclusive Development (GRID) approach, which departs from previous development strategies by promoting economic growth that goes hand in hand with environmental goals and social inclusion. Pursuing the twin goals of poverty eradication and shared prosperity with a sustainability lens, the GRID approach addresses the risks to people, the planet, and the economy in an integrated manner that is tailored to country needs and objectives. It sets a path that achieves lasting economic progress that is shared across the population, providing a robust recovery, and restoring momentum on the Sustainable Development Goals (SDGs). As countries face a historic opportunity to establish a better way forward, they will need to make significant reforms, mobilize domestic resources fairly, and deploy private sector solutions at scale. To ensure that the fruits of these transformations are evenly distributed, a range of social and labor market policies are also needed to compensate losers, safeguard the vulnerable, and deliver a just transition to a green economy. As needs are vast, complementary involvement from the public and private sectors, and the international community is vital